Multimedia Interaktif Pengenalan Objek Wisata Kota Pagar Alam - Medi Triawan; Heriansyah, Heriansyah (Jurnal Ilmiah Binary STMIK Bina Nusantara Jaya, 2022)
Tourism is a trip or as part of these activities carried out voluntarily and temporarily to enjoy tourist objects and attractions. Pagar Alam City is a city located in South Sumatra Province which has many potential tourism objects. The city is a tourist destination with an area of ​​633.66 Km² or 63,366 Ha. Strengths of attraction such as culture, history, good climate, friendly people make Pagar Alam City have a high level of visitor enthusiasm. The lack of information and promotional media carried out by the Pagar Alam City government on the potential of tourism objects causes the city of Pagar Alam to be less well known with a myriad of tourist attraction assets owned. With the Interactive Multimedia application for Introduction to Tourism Objects in Pagar Alam City which was built with Adobe Flash Cs6 which was exported to the "PesonaIndahWisataPagarAlam.apk" file using the Multimedia Development Life Cycle (MDLC) method which consists of six stages starting from the Concept stage, design, obtaining content material, assembly, testing, and distribution are expected to increase the number of visitors who come to the city of Pagar Alam